1996
DOI: 10.1037/0022-006x.64.4.819
|View full text |Cite
|
Sign up to set email alerts
|

Safer sex: Social and psychological predictors of behavioral maintenance and change among heterosexual women.

Abstract: Women of diverse backgrounds from 4 community health clinics in southern Connecticut were involved in a longitudinal, prospective study (n = 189). Data from interviews 3 months apart were used for the current analyses. The purpose of this study was to develop predictive models of safer sexual behavior among heterosexual women. Specifically, there was an interest in identifying factors to predict the maintenance or initiation of safer behavior over time. Relationship involvement and attitudes toward condoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
58
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 31 publications
13
58
0
2
Order By: Relevance
“…Thus, optimism might serve as a buffer for individuals with prior negative childhood healthcare experiences. Consistent with other work (Morrill et al, 1996;Taylor, Kemeny, Aspinwall, Schneider, & Rodriguez, 1992), an optimistic style might influence healthcare behavior and/or impressions of healthcare behavior. In the current study optimism was positively associated with childhood healthcare experiences; this relation has not been previously investigated in the literature.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Thus, optimism might serve as a buffer for individuals with prior negative childhood healthcare experiences. Consistent with other work (Morrill et al, 1996;Taylor, Kemeny, Aspinwall, Schneider, & Rodriguez, 1992), an optimistic style might influence healthcare behavior and/or impressions of healthcare behavior. In the current study optimism was positively associated with childhood healthcare experiences; this relation has not been previously investigated in the literature.…”
Section: Discussionsupporting
confidence: 61%
“…For example, negative healthcare attitudes increased the likelihood of engaging in negative healthcare behaviors (i.e., avoidance of medical visits, fear of medical procedures; Bachanas & Roberts, 1995;Pate et al, 1996;Peterson et al, 2002). Similarly, positive attitudes toward condoms have been associated with better adherence to condom use (Morrill, Ickovics, Golubchikov, & Beren, 1996). However, there is a lack of research on the relationships between healthcare attitudes and other specific positive healthcare behaviors (e.g., diet, exercise).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, there is evidence that condom use is more common among persons involved in relationships with decreased intimacy and feeling less love for their partners (Aalsma, Fortenberry, Sayegh, & Orr, 2006;Civic, 1999). Moreover, condom use or reduced frequency of PVI without condoms have been associated with more use of immature defense mechanisms , depression (Gallup, Burch, & Platek, 2002;Morrill, Ickovics, Golubchikov, Beren, & Rodin, 1996;Smit et al, 2006), poorer immune function (Peters et al, 2004) and higher body mass index (Akers et al, 2009). A series of studies have shown a relationship of history of condom use or coitus interruptus with greater risk of breast cancer (Gjorgov, 1978(Gjorgov, , 1998Le et al, 1989;Vessey et al, 1983).…”
Section: The Downside Of Condom Use During Pvimentioning
confidence: 99%